Електронна будова і стабільність фаз дигідриду магнію - Uvarov, V.N.; Uvarov, N.V.; Melnik, M.P.; Nemoshkalenko, M.V. (Publishing house "Academperiodika", 2022)
With the help of band calculations in the framework of the full-potential linearized augmentedplane-wave model, information on the energy characteristics, the charge states of atoms, the nature of chemical bonds, the structure of valence bands, and the conductivity bands of polymorphous modifications of magnesium dihydride has been obtained. It is found that all magnesium dihydride phases are nonmagnetic insulators, with the electronic states of the metal and hydrogen atoms being hybridized within the whole energy interval of both the valence and conduction bands. It is shown that a reduction in the total charge of electrons in the interatomic region leads to a decrease in the cohesive energies of high-pressure magnesium dihydride phases, which are factors favoring the improvement of their hydrogen desorption kinetics.